A piglet named Mercy - DiCamillo, Kate; Van Dusen, Chris (Somerville, Massachusetts : Candlewick Press, 2019)
When a pig named Mercy arrives at the Watsons' front door, she brings love and chaos to their lives.
Keywords: Pigs -- Fiction; Pigs -- Fiction